Risk prediction of cardiovascular event using WHO/ISH chart and awareness regarding the cardiovascular risks among adult population in rural areas of Krishnagiri district, Tamil Nadu: a cross-sectional study - Chakravarthy, Nithin; Thuruthayil, Ashima K.; Keerthana, Emmadi; Fathima, Farah Naaz (International Journal Of Community Medicine And Public Health, 2025)
Introduction: Identification of risks and increasing awareness levels is essential for primary and secondary prevention of cardiovascular diseases (CVD). Our study focused on distribution of risk for cardiovascular events and the awareness levels among the rural adult population. Method: A cross-sectional study was conducted among 220 participants in ten selected villages in Hosur, Krishnagiri district. Participants aged above 40 years were selected by systematic random sampling with allocation proportional to village population. Data were collected using a pre-tested questionnaire, anthropometric measurements, and laboratory investigations. WHO/ISH chart (laboratory based) was used to predict 10 years risk for CVD and ABCD questionnaire containing 4 domains with total score of 80 was used to assess the awareness for CVD risks. Results: The mean age of the participants was 53.4±9.6 years, and 30% were males. The study predicted that 20% (95% CI:14.2%-25.2%) of the participants were at moderate-high risk for CVD. The mean score for awareness was 50.0±4.6. Those divorced/separated (X2=25.3, p <0.001) had a significant high risk for CVD. Those with education above high school (F=3.3, p=0.014), non-tobacco users (t=4.5, p=<0.001), and hypertensives (t=2.2, p=0.023) had higher awareness levels. Conclusion: The proportion of population at moderate-high risk for CVD was 20%. Awareness regarding CVD risks was 50.0±4.6(out of 80). Use of WHO/ISH chart at grass root level will help in the identification of individuals at moderate to high risk. Regular health education sessions in the community are needed to enhance awareness levels.